Protective immunity against Nippostrongylus brasiliensis requires antigen presentation by IL-4Rα responsive B cells - Darby, Matthew G (University of Cape Town, 2015)
Includes bibliographical references. === Nippostrongylus brasiliensis is a parasitic nematode infection that affects rodents. B-cells have been shown to play an important role in immunity to many different infections by antibody production and T-cell activation. But B-cell function in the protective TH2 response against N. brasiliensis infection is an area of immunity that is currently not well defined. Recently, it has been shown that B-cells are essential to the resolution of a Heligomosomoides polygyrus infection, another parasitic helminth. Our aim in this study was to investigate any role that B-cells may play in response to a secondary N. brasiliensis infection by analysing the differences in immunity of wild-type and B-cell-specific IL-4RÎ± knockout mice after a N. brasiliensis re-infection.